Factors Found on the First Variceal-Bleeding Episode in Liver Cirrhosis Patients with Portal Hypertension - Arnold Hasahatan Harahap; Dadang Makmun; Irsan Hasan (The Indonesian Society for Digestive Endoscopy, 2010)
Background: The dietary protein restriction that was commonly recommended to hepatic encephalopathy (HE) patients, often leads to malnutrition, whereas malnutrition can deteriorate cirrhosis prognosis. The aims of this study were to find out encephalopathy improvement that was measured by critical flicker frequency (CFF) test and nutritional status by measuring prealbumin level after L-Ornithine L-Aspartate (LOLA) treatment with adequate calories and protein intake in patients with HE. Method: Patients with liver cirrosis who visited Cipto Mangunkusumo hospital on June-October 2009 was evaluated by CFF test using HEPAtonormTM device. Encephalopathy was defined when CFF 39 Hz. Nutritional status was measured by the mid-arm muscle circumference (MAMC) and was stated as malnutrition when the MAMC was below the 15th percentile. Patients had been treated by 3 x 6 mg LOLA granules for 2 weeks, and adequate calories and protein intake with branched-chain amino acid (BCAAs) substitution. The change of encephalopaty was evaluated by the CFF test and the nutritional status by measuring prealbumin blood level. Results: There were 17 patients with liver cirrhosis who fulfilled the inclusion criteria. The mean CFF Result increased from 34.1 ± 2.5 Hz to 36.5 ± 2.9 Hz after LOLA treatment with the adequate calories and protein intake including BCAAs substitution, which was statistically significant (p 0.001) compared to before treatment. The prealbumin level also increased significantly compared before treatment, i.e. from 5.4 ± 2.1 mg/dL to 6.4 ± 2.6 mg/dL, p = 0.008. Conclusion: HE patients with malnutrition could be given adequate calorie and protein with BCAAs substitution to improve their nutritional status, and LOLA granules for the improvement of HE. Keywords: minimal hepatic encephalopathy, malnutrition, CFF, LOLA, prealbumin, BCAAs